Financial stability considerations in the conduct of monetary policy - Paul Bochmann; Daniel Dieckelmann; Stephan Fahr; Josef Ruzicka (European Central Bank (ECB), 2023)
We empirically analyze the interaction of monetary policy with financial stability and the real economy in the euro area. For this, we apply a quantile vector autoregressive model and two alternative estimation approaches: simulation and local projections. Our specifications include monetary policy surprises, real GDP, inflation, financial vulnerabilities and systemic financial stress. We disentangle conventional and unconventional monetary policy by separating interest rate surprises into two factors that move the yield curve either at the short end or at the long end. Our results show that a build-up of financial vulnerabilities tends to be accompanied initially by subdued financial stress which resurges, however, over a medium-term horizon, harming economic growth. Tighter conventional monetary policy reduces inflationary pressures but increases the risk of financial stress. We find unconventional monetary policy to be similarly effective in reducing inflation, but with a lower adverse effect on growth and financial stress. Tighter unconventional monetary policy is also found to have a dampening effect on the build-up of financial vulnerabilities.
Keywords: E31; E52; G01; G10; 330; monetary policy; financial stability; macroprudential policy; quantile regressions; monetary policy identification